A general equilibrium model of bilateral trade with strategic public investment in commercial infrastructure. Issue 6 (18th August 2019) - Yen, Meng-Fen; Wu, Ruohan; Miranda, Mario Javier
ABSTRACT: We explore how public investment in commercial infrastructure affects the composition of trade between countries. To this end, we develop a model of bilateral trade in which two countries produce, consume, and trade a continuum of goods. Goods are produced by a single homogeneous factor, labor, the productivity of which depends on the quality of the country's commercial infrastructure, broadly conceived to encompass transportation, communication, and power transmission networks; regulatory and legal institutions; and basic research and educational systems. Countries may improve the quality of their commercial infrastructures through increased public investment. However, returns on these investments are constrained by fixed 'natural' endowments, with the better-endowed country enjoying greater labor productivity for a given level of public investment. We begin by analyzing optimal investment in public infrastructure in one country when public investment by the trading partner is fixed. We find that, ceteris paribus, greater public investment in commercial infrastructure raises general labor productivity, leading to gains in workers' real income. We then analyze a non-cooperative game in which both countries strategically vary public investment in commercial infrastructure. We find that, in a Nash game, the better-endowed country optimally spends more on infrastructure and produces the goods requiring the greatest labor productivity. However, in a Stackelberg game, the results are ambiguous. An empirical analysis based on recent international trade data supports our theoretical finding that investment in public infrastructure is positively related to the export of 'high-end' goods.